OPTIMIZING SME OPERATIONS THROUGH A WEB-BASED BREAD ORDERING SYSTEM: INTEGRATION OF WATERFALL METHODOLOGY AND LARAVEL FRAMEWORK FOR ENHANCED EFFICIENCY - Khair Rakhman, Ligian; Faridi; Ariestiandy, Deny; Lizsa, Zain (Buana Informatika, 2025)
UMKM Roti Maryam Opay, located in Sukabumi, still uses a manual ordering system through WhatsApp or by customers coming directly to the production site. This system has many limitations, such as unstructured order recording, a high risk of data entry errors, and difficulties in summarizing daily, weekly, and monthly orders. In addition, customers find it difficult to place orders outside working hours or from certain areas. To address these problems, the author designed and developed a web-based bread ordering application using the Laravel framework and MySQL database. The application development follows the Waterfall method, which consists of requirement analysis, system design, program implementation, program testing, and program maintenance. In the analysis phase, the author conducted direct observation and interviews with the business owner to understand the ongoing ordering process. The analysis results showed that the manual system caused inefficiencies and inconveniences for both admins and customers. In the design phase, UML was used to create important diagrams such as Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. The database structure was designed using ERD to clarify table relationships. The application features include user login and registration, product and bread variant management, ordering process with detailed delivery addresses, order management by admins, and automatic, structured transaction reports daily, weekly, and monthly.